Análisis del apremio personal hacia el alimentante que deba pensiones alimenticias; y, la vulneración del derecho constitucional a la libertad - Valarezo Torres, Juliana Elizabeth (2022)
The degree thesis entitled “Analysis of the personal compulsion towards the provider who owes child support; and, the vulnerability of the constitutional right to freedom”, the personal compulsion has been considered a relevant problem in society that has affected people who alimony payments owed. In the study of the compulsion, the majority of people consider that unemployment does not allow them to fulfill their obligation, in the development of the investigation, surveys and interviews were carried out with legal professionals. It should be emphasized that both the right of children and the right to freedom constitute guarantees in the Constitution of the Republic of Ecuador, in the Universal Declaration of Human Rights in its article 3, which stipulates the following: "Every individual has the right to freedom and their self-safety”, in this Convention as in other International Instruments, it is denoted that the right of freedom is over material goods. These two rights, besides being guaranteed in the Constitution of the Republic of Ecuador, they are also found in International Conventions, such as the Convention on the Rights of the Child, which primarily refers to and emphasizes the principle of the best interests of the child, it serves as a tool enabling them to enact their rights through laws. In other countries, such as Peru, Spain, and Colombia, the principle of the Best Interest of the Child, it is not applied to deprive people of freedom who owed alimony, at the moment that a person is going to be deprived for non-payment of alimony, people who represent children and teenagers must resort a legal action.